Thresholding of cryo-EM density maps by false discovery rate control - Beckers, Maximilian; Jakobi, Arjen; Sachse, Carsten (IUCrJ, 2019)
The interpretation of cryo-EM density by atomic models remains a daunting task owing to the identification of appropriate threshold levels at low signal-to-noise ratios in high-resolution shells and weak structural features. It is shown that transforming cryo-EM densities to confidence maps followed by false discovery rate-based thresholding provides a robust way to interpret cryo-EM structures.